Pengaruh Disiplin Belajar, Kecerdasan Emosional, Perhatian Orang Tua, Kemandirian Belajar dan Teman Sebaya Terhadap Prestasi Belajar Ekonomi Siswa Kelas XI SMA Pembangunan Laboratorium UNP - Sati, Putri Laras; Amluis, Dina; Ronald, Jimi (Jurnal Horizon Pendidikan, 2022)
This study aims to determine the effect of one variable with other variables and use the Stratified Random Sampling technique with a sample of 73 students. The results showed that: 1), learning discipline had a significant effect on learning achievement. Where indicated by the coefficient value of 0.591. This coefficient value is significant because the thitung value is 3.543 ttabel is 1.66980. 2), emotional intelligences have a significant effect on learning achievement. Where indicated by the coefficient value of -0.353. This coefficient value is significant because the value of thitung is -2.441 ttabel of 1.66980. 3), parents' attention has a significant effect on learning achievement. Where indicated by the coefficient value of -0.184. This coefficient value is significant because the value of thitung -1.919 ttabel is 1.66980. 4), independent learning have a significant effect on learning achievement. Where indicated by the coefficient value of 0.259. This coefficient value is significant because the thitung value is 2,680 ttabel is 1,66980. 5), peers have a significant effect on learning achievement. Where indicated by the coefficient value of -0.170. This coefficient value is significant because the value of thitung -1.959 ttabel is 1.66980. 6), learning disciplines, emotional intelligence, parental attention, independent learning, and peers together have a significant effect on learning achievement. Where obtained by the value of F-count 8.227 > F-table 2.31 with a significant level of 0.000 < = 0.05. This means that Ha is accepted and H0 is rejected.